Aktivitas Dinamis pada Appreciative Game “Warik the Adventurer” berbasis Finite State Machine - Naufal, Muhammad Rakha'; Haryanto, Hanny; Hastuti, Khafiizh; Nathania, Nita Virena (Journal of Applied Computer Science and Technology, 2024)
Serious games have become potential tools for education due to their advantage of giving a fun experience to the learner. Therefore, game experience is a fundamental element in serious game design. The game experience is mainly produced by the game activity, such as a quest or mission. However, in many serious games, the game activities do not have a clear design and concept, resulting in a poor playing experience which produce poor understanding of the material. Appreciative Game is a game that is based on Appreciative Learning concept. Appreciative Learning concepts could be used to design game activities. Appreciative Learning consists of four main stages. The stages are discovery, dream, design, and destiny. These four stages lay down the foundation of serious game activity. This study uses the Finite State Machine to produce intelligent agents in order to develop more dynamic game activity to enhance the game experience. We developed a 3D game called Warik the Adventurer as the testbed for this research. The game is about the cultural diversity in Indonesia. The game Experience Questionnaire (GEQ) is used to evaluate the player experience. The GEQ resulted in an acceptable score of 3 out of 5.